Invention Pedagogy - The Finnish Approach to Maker Education - Korhonen, Tiina; Kangas, Kaiju; Salo, Laura (Routledge Research in STEM Education, 2023)
This collection, edited and written by the leading scholars and experts of innovation and maker education in Finland, introduces invention pedagogy, a research-based Finnish approach for teaching and learning through multidisciplinary, creative design and making processes in formal school settings. The book outlines the background of, and need for, invention pedagogy, providing various perspectives for designing and orchestrating the invention process while discusses what can be learnt and how learning happens through inventing. In addition, the book introduces the transformative, school-level innovator agency needed for developing whole schools as innovative communities. Featuring informative case study examples, the volume explores the theoretical, pedagogical, and methodological implications for the research and practice of invention pedagogy in order to further the field and bring new perspectives, providing a new vision for schools for decades to come. Intermixing the results of cutting-edge research and best practice within STEAM-education and invention pedagogy, this book will be essential reading for researchers, students, and scholars of design and technology education, STEM education, teacher education, and learning sciences more broadly.